How Does Public Service Motivation Contribute to Service Orientation? Testing Mediation Models - Wayu Eko Yudiatmaja (Otoritas : Jurnal Ilmu Pemerintahan, 2019)
Public service motivation is an emerging topic in the study of public administration, but no study has adequately investigated how it affects employee service orientation through job satisfaction and organizational commitment. The present study is ultimately aimed to fill the research gap by examing whether public service motivation influences service orientation and if so, whether the effect is mediated by job satisfaction and organizational commitment. Data were analyzed by using WarpPLS 6.0. Using a sample of 160 public servants in the city government of Tanjungpinang, the results indicate that employee service orientation is directly and positively affected by PSM. In addition, public service motivation also has an indirect impact on employee service orientation through job satisfaction and organizational commitment. Furthermore, the theoretical and practical implications of the study for human resources management in the public sector are discussed.